2015
DOI: 10.1186/s12936-015-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

Prescription practices for malaria in Mozambique: poor adherence to the national protocols for malaria treatment in 22 public health facilities

Abstract: BackgroundCurrent World Health Organization and national protocols recommend the ‘test and treat’ strategy for the management of uncomplicated malaria, to reduce over prescription of artemisinin-based combination treatment (ACT). Therefore, adherence to these protocols varies in different sub-Saharan African countries and no information is available for Mozambique. This study was conducted with the aim to evaluate the prescription practices of ACT in Mozambique.MethodsRetrospective audit of medical records cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Of note, despite all five patients who met the definition of acute leptospirosis having negative malaria results, four of them (80.0%) were treated with antimalarials. This highlights that malaria is over-diagnosed in Mozambique, as demonstrated previously (Salomao et al, 2015). Improvements to the national algorithms for fever and malaria management are urgently needed in Mozambique in order to avoid the inappropriate use of antimalarials and to ensure that patients receive the correct treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Of note, despite all five patients who met the definition of acute leptospirosis having negative malaria results, four of them (80.0%) were treated with antimalarials. This highlights that malaria is over-diagnosed in Mozambique, as demonstrated previously (Salomao et al, 2015). Improvements to the national algorithms for fever and malaria management are urgently needed in Mozambique in order to avoid the inappropriate use of antimalarials and to ensure that patients receive the correct treatment.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, over-prescription of malaria drugs has implications for the emergence of parasite drug resistance, an important global concern [33]. Despite all this, malaria overdiagnosis remains a well-documented yet persistent issue in SSA resulting in over-inflation of actual malaria rates reported at the local and national levels [1114]. …”
Section: Discussionmentioning
confidence: 99%
“…perceptions of high malaria endemicity and any fever being equivalent to malaria) and issues related to laboratory testing [1114]. The gold standard for malaria diagnosis is microscopic examination of blood smears.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of medical records is a major limiting factor when conducting retrospective studies; similar limitations have been reported elsewhere. 28 Data on clinically treated cases of malaria were not available because the database was derived from active case investigations conducted after reports of a confirmed case. Furthermore, the pregnancy status of some of the female cases was not recorded and the reasons for this were not provided.…”
Section: S6mentioning
confidence: 99%